1997
DOI: 10.1111/j.1750-3639.1997.tb01080.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuroschistosomiasis

Abstract: Schistosomiasis is an infection caused by digenetic trematode platyhelminths of the genus Schistosoma. These blood flukes use man and other mammals as definitive hosts and aquatic and amphibious snails as intermediate hosts. Of the schistosomal species, S. mansoni, S haematobium and S. japonicum are the most important to man and the most widely distributed. The infection affects about 200 million individuals in 74 countries of Latin America, Africa and Asia. Far less commonly, schistosomes reach the central ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
126
0
7

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 137 publications
(133 citation statements)
references
References 75 publications
0
126
0
7
Order By: Relevance
“…There are 2 main mechanisms of cerebral NS: egg embo-lization (indirect deposition) and adult worm migration (direct deposition) [6][7][8][9] . haematobium can also induce similar symptoms.…”
Section: The Cerebral Nsmentioning
confidence: 99%
See 4 more Smart Citations
“…There are 2 main mechanisms of cerebral NS: egg embo-lization (indirect deposition) and adult worm migration (direct deposition) [6][7][8][9] . haematobium can also induce similar symptoms.…”
Section: The Cerebral Nsmentioning
confidence: 99%
“…However, disorder caused by S. mansoni is not so common as that by S. japonicum, and disorder caused by S. haematobium is even rare [5] . Pittella [8] has reported that the schistosoma adult worms begin laying eggs after mature, and the majority of the eggs deposit in the portal system and the pulmonary system through the arteriovenous anastomosis. Then the eggs enter the pulmonary vein, reaching the brain through the arterial system.…”
Section: The Cerebral Nsmentioning
confidence: 99%
See 3 more Smart Citations